What hinders the development of Chinese continuing care retirement community sector? A news coverage analysis - Hu, Xin; Xia, Bo; Hu, Yi; Skitmore, Martin; Buys, Laurie (International Journal of Strategic Property Management, 2019)
The continuing care retirement community (CCRC) is an emerging institutional living arrangement for the increasing number of older Chinese and has attracted a variety of investors from different sectors in China. However, the development of this sector is still in its infancy and encounters various barriers. This paper aims to explore what hinders the development of the Chinese CCRC industry based on a comprehensive content analysis of news coverage retrieved from 14 major Chinese portal websites. Twenty-one barriers are identified, and they are closely related to the development and operation of CCRCs, government policies and industry management, and potential and current customers. Of all the barriers, the high risks involved in the delivery of CCRCs, lack of policy support, and affordability issue are the most frequently mentioned barriers relating to CCRC development and operation, government policies and industry management, and customers, respectively. These identified barriers call for close collaboration cross various CCRC stakeholders in order to ensure healthy development of the Chinese CCRC industry in the future. This study systemically explores the barriers hindering the development of the burgeoning Chinese CCRC sector, and its findings will benefit CCRC stakeholders and the Chinese CCRC industry in a number of ways.